Vγ4+γδT Cells Aggravate Severe H1N1 Influenza Virus Infection-Induced Acute Pulmonary Immunopathological Injury via Secreting Interleukin-17A - Xue, Chunxue; Wen, Mingjie; Bao, Linlin; Li, Hui; Li, Fengdi; Liu, Meng; Lv, Qi; An, Yunqing; Zhang, Xulong; Cao, Bin (Frontiers in Immunology, 2017)
The influenza A (H1N1) pdm09 virus remains a critical global health concern and causes high levels of morbidity and mortality. Severe acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are the major outcomes among severely infected patients. Our previous study found that interleukin (IL)-17A production by humans or mice infected with influenza A (H1N1) pdm09 substantially contributes to ALI and subsequent morbidity and mortality. However, the cell types responsible for IL-17A production during the early stage of severe influenza A (H1N1) pdm09 infection remained unknown. In this study, a mouse model of severe influenza A (H1N1) pdm09 infection was established. Our results show that, in the lungs of infected mice, the percentage of γδT cells, but not the percentages of CD4+Th and CD8+Tc cells, gradually increased and peaked at 3 days post infection (dpi). Further analysis revealed that the Vγ4+γδT subset, but not the Vγ1+γδT subset, was significantly increased among the γδT cells. At 3 dpi, the virus induced significant increases in IL-17A in the bronchoalveolar lavage fluid (BALF) and serum. IL-17A was predominantly secreted by γδT cells (especially the Vγ4+γδT subset), but not CD4+Th and CD8+Tc cells at the early stage of infection, and IL-1β and/or IL-23 were sufficient to induce IL-17A production by γδT cells. In addition to secreting IL-17A, γδT cells also secreted interferon (IFN)-γ and expressed both an activation-associated molecule, natural-killer group 2, member D (NKG2D), and an apoptosis-associated molecule, FasL. Depletion of γδT cells or the Vγ4+γδT subset significantly rescued the virus-induced weight loss and improved the survival rate by decreasing IL-17A secretion and reducing immunopathological injury. This study demonstrated that, by secreting IL-17A, lung Vγ4+γδT cells, at least, in part mediated influenza A (H1N1) pdm09-induced immunopathological injury. This mechanism might serve as a promising new target for the prevention and treatment of ALI induced by influenza A (H1N1) pdm09.